2011
DOI: 10.1089/rej.2011.1197
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Administration of Human Umbilical Cord Blood Cells Delays Disease Progression in Two Murine Models of Motor Neuron Degeneration

Abstract: The lack of effective drug therapies for motor neuron diseases (MND), and in general for all the neurodegenerative disorders, has increased the interest toward the potential use of stem cells. Among the cell therapy approaches so far tested in MND animal models, systemic injection of human cord blood mononuclear cells (HuCB-MNCs) has proven to reproducibly increase, although modestly, the life span of SOD1G93A mice, a model of familial amyotrophic lateral sclerosis (ALS), even if only few transplanted cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…Again, and in keeping with previous findings (Bigini et al, 2011), the appearance of transplanted cells, never showing morphological features of mature neurons, nor expressing any neuronal markers either, strongly suggest that, as outlined above, they may act via the production and release of locally acting factors with protective and/or anti-inflammatory properties, rather than by replacement of degenerating neurons.…”
Section: Transplantation Of Msc In Experimental Amyotrophic Lateral Ssupporting
confidence: 86%
See 1 more Smart Citation
“…Again, and in keeping with previous findings (Bigini et al, 2011), the appearance of transplanted cells, never showing morphological features of mature neurons, nor expressing any neuronal markers either, strongly suggest that, as outlined above, they may act via the production and release of locally acting factors with protective and/or anti-inflammatory properties, rather than by replacement of degenerating neurons.…”
Section: Transplantation Of Msc In Experimental Amyotrophic Lateral Ssupporting
confidence: 86%
“…This provides support to the hypothesis that the restoring effects of transplanted cells in not due to cell replacement per se but, rather, it is associated with the production and release of circulating protective factors that may act both ad the CNS and PNS levels. In fact it has been shown that implanted MSCs release a series of cytokines and chemokines with anti-inflammatory properties that could be responsible of the functional improvement of mouse models of motor neuron degenerative disorder (Bigini et al, 2011;Uccelli et al, 2012).…”
Section: Transplantation Of Msc In Experimental Amyotrophic Lateral Smentioning
confidence: 99%
“…As a matter of fact we have already demonstrated that ICV injection of SCs in two different ALS animal models (SOD1G93A and wobbler mice) resulted in significant therapeutic improvements although no cell localization in the pathological tissue was observed [6]. Moreover, intrathecal and intravenous SC administration have already been tested in a preliminary clinical trial aimed at demonstrating the safety and immunological effects of mesenchymal SC transplantation in patients with multiple sclerosis and ALS [34].…”
Section: Discussionmentioning
confidence: 99%
“…The route of administration of stem cells needs to be pre-determined: systemic [21] , intracerberoventricular [22] , and local injection [23][24][25][26][27][28] . Upon systemic injection, transplanted stem cells migrated to the damaged areas in SOD1G93A mice [22] .…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Upon systemic injection, transplanted stem cells migrated to the damaged areas in SOD1G93A mice [22] . Neural precursor cells transplanted specifically into the cervical spinal cord ventral gray matter of both SOD1G93A rats survived [29] .…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%